The Effect of Boss Cap Fins to B – Series Propeller Performance With CFD Method - Amiadji; Achmad Baidowi; Achdri Fauzi Nugraha Oloan (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2018)
Propeller is similar to rotating fan blade with having primary function as propulsion system. In order to increase propeller performance, Engineer is developing Energy Saving Devices (ESD) to reduces operational cost, clean energy and for long term utilization. The global emmision from marine is 2.7 % in 2007. One of ESD is Propeller Boss Cap Fins (PBCF). The focus of this thesis is to design and developed PBCF B - series propeller. This thesis studies the performance of a propeller without and with PBCF such as efficiency, thrust, torsion and dynamic hub vortex phenomenon. To obtain the results this thesis uses Computational Fluid Dynamic (CFD). The PBCF simulations were based on its pitch angle. The simulation results shows that PBCF is achieved the highest efficiency which is 0.60 %, and increases thrust 3.21 %, and torsion increase 2.64 % compared to propeller without PBCF. It also shows that the PBCF is able to break the vortex flow and it will reduces the porosity to the rudder and decrese the corrosion potention to the rudder.